Artistic features of real and imagined in dystopian films (Eurasian Journal of Media and Communications, 2022)
The concept of dystopia is one of the concepts that have been used for a long time, but it has been widely circulated in recent times in various types of arts and literature as a result of major global events and the outcome of political, social, economic conditions and others, which mainly reflected on human life and the nature of life, instead of life heading towards well-being And happiness with the development of science, thought and technology, you see, is heading towards hatred, despair and injustice, and because cinema is one of the arts that transmits phenomena and events experienced by society or that can be manifested in its ideas, even imaginary ones, many films have appeared that embody dystopia, whether at the level of form or topic and with treatments different cinematic .The research was divided into three sectionsThe first topic: the general concept of dystopiaThe second topic: dystopia in literature and the artsThe third topic: the manifestations of dystopia in the movie